2011 La Fonda Patrioootera - Grupo Teatro La Cochera (2017)
Idea: Paco Giménez | Actúan: Chacha Alvarado, Marcelo Castillo, Gabriela duran, Federico Franco, Alejandra Garabano, Vequi Gómez | Operación técnica: Lucas Solé | Dirección: Paco Giménez | Consultado el 21 de mayo de 2017 | http://www.alternativateatral.com/obra28705-la-fonda-patrioootera